The importance of palliative care in patients with breast cancer - Nascimento, Evelyn Cristine; Freitas, Vitória Gomes de; Silva, Lure Emilly Barreto da; Costa, Higor Siqueira; Rocha, Marina Elias (Mastology, 2026)
Objective: To analyze the importance of palliative care in patients with breast cancer. Methods: The search for articles was carried out on SciELO and PubMed databases, where ten original articles in Portuguese and English were found, published between 2020 and 2025, and using the descriptors “breast cancer” and “palliative care”, of which four were selected for review. Results: Palliative care in breast cancer aims to improve quality of life and alleviate symptoms regardless of the stage of the disease. For many years, this care was seen as a model that integrated the transition between life and death. More recently, it has come to be recognized as a broader approach, which focus on the quality of life of patients and their families in the face of the threat to continuity of life. The purpose is to alleviate suffering, which requires early identification, assessment, and appropriate treatment of the patient. This is accomplished through good communication, where attention is focused not only on pain but also on other problems of physical, psychosocial, and spiritual nature by listening to patient’s needs, promoting well-being, and supporting the family. According to a study carried out on breast cancer patients, it was found that palliative care contributed significantly to increasing their comfort, reducing anxiety and depression. In addition, it is also important to highlight that the early integration of this care into the treatment can favor the exercise of patient autonomy, as well as the participation of family members and health professionals in the decisionmaking process and shared planning of care in a comprehensive manner. Conclusion: In breast cancer, palliative care is an approach designed to improve the quality of life of patients and their families. Upon diagnosis, its objective is to prevent and alleviate suffering through early identification, appropriate assessment, and treatment of conditions, whether physical, psychosocial, or spiritual.